2020
DOI: 10.1063/5.0030279
|View full text |Cite
|
Sign up to set email alerts
|

Internal-strain release and remarkably enhanced energy storage performance in PLZT–SrTiO3 multilayered films

Abstract: The multilayered composite films combining antiferroelectric (AFE) Pb0.97La0.02(Zr0.95Ti0.05)O3 (PLZT) with paraelectric (PE) SrTiO3 (STO) have been fabricated by the sol–gel method, and their ferroelectric and energy storage performances were carefully investigated. It was revealed that both the dielectric breakdown strength (Eb) and the maximum polarization (Pm) in the multilayered composite films are increased. Consequently, an ultra-high and recoverable energy storage density (Wre) of ∼101 J/cm3 and a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Finally, the energy storage density and efficiency of the F8 film in this work are compared with the corresponding values of representative perovskite film capacitors in the recent 2 years, as shown in Figure i. It is suggested that the F8 film has a considerable role in perovskite energy storage, especially in the comparison of energy storage density.…”
Section: Results and Discussionmentioning
confidence: 82%
“…Finally, the energy storage density and efficiency of the F8 film in this work are compared with the corresponding values of representative perovskite film capacitors in the recent 2 years, as shown in Figure i. It is suggested that the F8 film has a considerable role in perovskite energy storage, especially in the comparison of energy storage density.…”
Section: Results and Discussionmentioning
confidence: 82%
“…With increased thickness of STO, the PLZT peak moves to higher angle, demonstrating increased compressive misfit constraint from the STO layer. [31] The cross sectional scanning transmission electron microscopy (STEM) of mica/CFO/SRO/PLZT 85 -STO 15 in Figure 2d reveals clear interfaces between each functional layer, though PLZT and STO cannot be distinguished. The total thickness of CFO/SRO/PLZT-STO is estimated to be 0.55 µm, consistent with AFM measurement, with the thickness of PLZT 85 -STO 15 superlattice estimated to be 0.49 µm.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, thin films [305] show much higher energy density than bulk materials due to the larger E BDS , as shown Fig. 11c [171,232,235,250,293,299, and 11d [20,89,99,144,181,233,[336][337][338][339][340][341][342][343][344][345][346][347][348][349][350][351][352].…”
Section: Energy-storage Capacitorsmentioning
confidence: 97%